VALIDATION OF STUDENT WORKSHEET CONTAINING SCIENTIFIC LITERACY FOR STRAIGHT MOTION MATERIALS - Dwi Yulianti; Renol Afrizon; Hidayati Hidayati; putri dwi sundari; Emiliannur Emiliannur (Universitas Negeri Padang, 2022)
The 21st century demands that students be able to have critical thinking competencies, communicate, relate global issues and literacy of scientific. Efforts made by the government to meet these demands are by improving the curriculum and holding the program of School Literacy Movement. But in reality there are problems related to literacy which is applied only to note and listen to the teacher, the unavailability of worksheets in all subjects, and the low understanding of students in answering questions. One way to deal with this issue is to develop a physics worksheet containing literacy in scientific. The research purpose was to determine of Characteristics of LKS containing literacy of scientific in straight motion material. This research type was design research (Design Research). The research object was the physics worksheet with literacy of scientific on the material of straight motion. The research instrument used was a self-evaluation assessment sheet, a one to one assessment sheet consisting of material components, learning design, implementation and technical. Expert validation sheet consisting of content, linguistic, presentation, and graphic feasibility components. The data analysis technique uses Aiken's formula to be able to calculate the content validity coefficient. The results of the LKS validation assessment obtained a value on the content feasibility component of 0.8 in the category was valid, the value on the linguistic feasibility component of 0.75 in the category was valid, the value on the presentation feasibility component of 0.77 in the category was valid, and the value on the feasibility component graphics of 0.83 in the category was very valid. Based on the results of research on physics worksheets containing literacy of scientific in the category was valid with an average validity value of 0.79.